HUBUNGAN TINGKAT PENGETAHUAN PROTOKOL KESEHATAN DENGAN KEJADIAN COVID-19 PADA KELUARGA BINAAN FK UMSU ANGKATAN 2018 - MUHAMMAD RIVAI PANJAITAN; MILA TRISNA SARI (JURNAL ILMIAH SIMANTEK, 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by a new type of coronavirus, namely Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which has never been identified in humans. Society now has to adjust to the pattern of life in the era of the COVID-19 pandemic. One of them is a new habit pattern regarding the discipline of the COVID-19 health protocol which aims to reduce the transmission of the COVID-19 virus outbreak by implementing the 5M health protocol. The high rate of transmission of COVID-19 cases in Indonesia is still caused by various problems. One of them is the lack of public concern, awareness and knowledge in maintaining cleanliness and protecting themselves from COVID-19. Determine the relationship between the level of knowledge of health protocols and the incidence of COVID-19 in families assisted by FK UMSU. This research is a cross sectional study. The research sample was taken using simple random sampling method, amounting to 30 people. The hypothesis test used was the Pearson Chi-square test with data collected based on a health protocol knowledge level questionnaire. Shows that there were 23 respondents (76.7%) respondents who had good knowledge and 27 respondents (90%) had never experienced COVID-19 (p value = 0.004). There is a relationship between the level of knowledge of health protocols and the incidence of COVID-19 in FK UMSU fostered families class of 2018.